2017
DOI: 10.1088/1361-6528/aa78e9
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tunable plasma nano-machining for fabrication of 3D hollow nanostructures: SERS application

Abstract: Novel processing sequences for the fabrication of artificial nanostructures are in high demand for various applications. In this paper, we report on a fine-tunable nano-machining technique for the fabrication of 3D hollow nanostructures. This technique originates from redeposition effects occurring during Ar dry etching of nano-patterns. Different geometries of honeycomb, double ring, nanotube, cone and crescent arrays have been successfully fabricated from various metals such as Au, Ag, Pt and Ti. The geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Moreover, for atomically flat surfaces at normal incidence, redeposition depends on the ion's mean free path length in the process chamber. 75 This is an extreme example, but it suggests that IBE at normal incidence only enables redeposition whenever the initial deposited material already has some roughness. Control over the redeposition rate is critical for the Au-HNP plasmonic structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, for atomically flat surfaces at normal incidence, redeposition depends on the ion's mean free path length in the process chamber. 75 This is an extreme example, but it suggests that IBE at normal incidence only enables redeposition whenever the initial deposited material already has some roughness. Control over the redeposition rate is critical for the Au-HNP plasmonic structures.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, Jeon et al 50 achieved similar 3D architectures with NIL, but in our case, we have pattern-ability by SHL and show the wafer-scale homogeneity. Lastly, Mehrvar et al 75 showed the complexity of using a capacitively coupled RIE for sidewall redeposition. Utilizing an IBE gives a more controllable platform for sidewall redeposition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The partial pressure of sputtered silicon is highest at the center of the SiNW, which results in a lower etch rate. Studies conducted on the redeposition of metals under a polymer mask subdued to CM-ICP RIE show that indeed the redeposition process is pressure-dependent [37]. To lower the probability of redeposition, the substrates were etched in an IBE system at a much lower process chamber pressure than that during CM-ICP RIE, being 0.17 mTorr instead of 18 mTorr.…”
Section: Comparison Of the Cm-icp Rie In Argon With Rat-ibe In Argonmentioning
confidence: 99%
“…In other literature works, maskless etching and sharpening of structures were suggested based on this electric field effect [36]. However, a more likely explanation for the observed tip formation and redeposition effect is the pressure range in which the inductively coupled plasma RIE (ICP RIE) functions [37]. The impeding argon ions (Ar + ) sputter the silicon which in turn increases the pressure and decreases the mean free path length near the surface, leading to a higher lateral velocity component near the substrate that enables sputter redeposition [38,39].…”
Section: Introductionmentioning
confidence: 97%